Profound Pneumocephalus and Low-Pressure Hydrocephalus Triggered by Ventriculoperitoneal Shunt Placement after Resection, Fat Graft Reconstruction, and Radiotherapy for a Malignant Skull Base Schwannoma - Stevens, Baylee; Bialek, Shannan; Zhao, Kyle; Maqusi, Suhair; Rassi, Edward El; Tan, Jeremy; Graffeo, Christopher S. (Journal of Neurological Surgery Reports, 2024)
Background Tension pneumocephalus is a rare postoperative complication, typically presenting with mental status changes or rapid neurological decline after craniotomy. We report a complex case of tension pneumocephalus triggered by graft retraction after ventriculoperitoneal (VP) shunt placement.Case History A 39-year-old woman with a recurrent left trigeminal cavernous sinus schwannoma, status post one prior resection, two stereotactic radiosurgery treatments, and one course of fractionated radiotherapy, underwent radical resection with orbital exenteration and abdominal fat free graft reconstruction followed by adjuvant radiotherapy for malignant transformation. She developed subacute ventriculomegaly with altered mental status, prompting VP shunt placement. Three weeks later, she presented with profound pneumocephalus and intraventricular air originating from a large, left-sided sphenoid and maxillary defect, from which the fat graft had retracted. A right frontal external ventricular drain (EVD) was placed, resulting in immediate release of air under high pressure. Definitive treatment required skull base reconstruction with a latissimus dorsi free flap, contralateral nasoseptal flap, antibiotics, and VP shunt revision for treatment of combined cerebrospinal fluid (CSF) leak, pneumocephalus, ventriculitis, and low-pressure hydrocephalus. As of her last follow-up, she was restored to her initial postresection neurological baseline.Conclusion Tension pneumocephalus is a rare and life-threatening emergency that requires immediate neurosurgical intervention. We report the index case of tension pneumocephalus induced by graft retraction following radiotherapy and CSF diversion. Where observed, tension pneumocephalus resulting from a skull base CSF leak may be associated with low-pressure hydrocephalus, and successful long-term management demands balancing the need for CSF diversion against the integrity of the skull base reconstruction.
Keywords: pneumocephalus; tension pneumocephalus; schwannoma; ventriculoperitoneal shunt; fat graft reconstruction; irradiation